ANALISIS PENGARUH NET PROFIT MARGIN DAN CURRENT RATIO TERHADAP DIVIDEND PAYOUT RATIO PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI PT. BURSA EFEK INDONESIA - Putu Tirta Sari Ningsih; Muhammad Gusvarizon; Nur Fadilla; Yohanes Bowo Widodo (Pusat Riset dan Inovasi Nasional, 2021)
This study aims to determine: (1) The effect of Net Profit Margin on Dividend Payout Ratio in manufacturing companies at PT. Indonesia stock exchange. (2) Effect of Current Ratio on Dividend Payout Ratio in manufacturing companies at PT. Indonesia stock exchange. (3) Effect of Net Profit Margin and Current Ratio on Dividend Payout Ratio in manufacturing companies at PT. Indonesia stock exchange. The research method is descriptive quantitative. In this study, there are two independent variables, namely Net Profit Margin and Current Ratio and one dependent variable, namely the Dividend Payout Ratio. The sampling technique used purposive sampling with a sample of 12 manufacturing companies registered at PT. Indonesia stock exchange. Data analysis used multiple regression analysis. Based on the results of data analysis obtained: (1) There is a joint influence between Net Profit Margin and Current Ratio on the Dividend Payout Ratio. (2) There is a significant effect of Net Profit Margin on the Dividend Payout Ratio. (3) There is a significant effect of Current Ratio on Dividend Payout Ratio.